2017
DOI: 10.1002/cite.201600151
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Influence of Filling Method and Particle Material on the Packed‐Bed Porosity

Abstract: The reliable prediction of the pressure drop of packed beds requires an accurate estimation of the packed-bed porosity as its error propagation multiplies the occurring errors by a factor of about four. The commonly used correlations to determine porosity depend only on the tube to particle diameter ratio. To improve accuracy, the influence of the filling method and of material properties, in particular surface roughness, density, and restitution coefficient are investigated for random packings of spheres in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…Several authors observed a significant variance between experimentally measured void fractions for the same reactor‐to‐particle diameter ratio 3, 10. The variations in ε might origin with decreasing influence from (i) the difference in position from which a particle falls into the tube, (ii) the difference in translational and rotational particle velocity at the start of the fall, (iii) the difference in the time interval between two drops, and (iv) differences in single‐particle properties, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors observed a significant variance between experimentally measured void fractions for the same reactor‐to‐particle diameter ratio 3, 10. The variations in ε might origin with decreasing influence from (i) the difference in position from which a particle falls into the tube, (ii) the difference in translational and rotational particle velocity at the start of the fall, (iii) the difference in the time interval between two drops, and (iv) differences in single‐particle properties, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…While the impact of frictional forces on bed voidage is widely accepted, only little data exists on the impact of particle mass or its density. Pottbäcker and Hinrichsen studied experimentally the impact of different material properties on bed voidage and suspected that the coefficient of restitution and the particle density might affect the bed voidage. However, not all data fit to their hypothesis, for example, for spheres of rusty steel and polyoxymethylene the resulting bed voidage is equal, although, particle density is more than five times higher for steel, and static friction coefficients are similar.…”
Section: Methodsmentioning
confidence: 99%
“…Random particles within a fixed‐bed reactor show a loosening, i.e., an increase of the local packing porosity near to the wall, and thus, an uneven distribution of the catalyst phase, which cannot be neglected especially with small D i /d p ratios. , , , …”
Section: Methods For Experimental Model Validationmentioning
confidence: 99%